THE EDUCATION OF ISLAM AND THE ADOLESCENT MENTAL HEALTH IN THOUGHT ZAKIAH DARAJAT - Santi Aisah Sihotang (Journal Analytica Islamica, 2020)
Abstract: Islamic education is an education system that can give one's ability to pin their lives in accordance with the ideals and values of Islam that have been animated and color the pattern of his personality. Basicly in shaping and moral development of children in need of guidance and teaching and the application of Islamic religious education, as a benchmark that parents want. This type of research is library Research, which is a study done by searching and discussing literature or related books. The source of the data used is the books of Zakiah Darajat as the primary data source and other books relating to the research object as a data source of seconders. The results showed that: (a). Education is a teaching activity, giving examples, training skills, motivating, and creating social environments that support the implementation of personal formation ideas. (b) Religion is the rules of God Almighty. With the dimension of vertical and Horizontal capable of encouraging human souls that are resourceful to be guided according to the laws of God with his own will, without being influenced, to achieve the happiness of life in the world and the hereafter. (c) Adolescent mental health begins with adolescent religious education that begins with the family, because with mental health developed by good religious education, will be able to direct his life more directed, and be a qualified person, in terms of creed, faith, Taqwa, and his absence.Keywords: Education, Religion and adolescent Mental Health